Viktor Mozalevsky’s memoirs - Alexander Sobolev (Литературный факт, 2019)
Memoirs of the writer Viktor Ivanovich Mozalevsky (1889– 1970) are for the first time published in full and with detailed commentary. Being an unobtrusive, but active participant of literary life since the mid-1900s, Mozalevsky left vivid literary portraits of V. Bryusov, B. Sadovskoy, Yu. Slezkin, S. Auslender, E. Nagrodskaya, M. Bulgakov and many others.